2006
DOI: 10.1111/j.1527-3458.2006.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Humanin and Colivelin: Neuronal‐Death‐Suppressing Peptides for Alzheimer's Disease and Amyotrophic Lateral Sclerosis

Abstract: Humanin (HN), a 24-amino-acid neuroprotective peptide, was originally found in the occipital lobe of an autopsied Alzheimer's disease (AD) patient. HN inhibits neuronal death by binding to its specific receptor on the cell membrane and triggering a Jak2/STAT3 prosurvival pathway. The activation of this pathway may represent a therapeutic approach to AD. HN also exhibits neuroprotective activity against toxicity by familial amyotrophic lateral sclerosis (ALS)-related mutant superoxide dismutase (SOD1). Recent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…Colivelin, consisting of ADNF and AGA-(C8R)HNG17, exhibits its neuroprotective activity by activating both ADNF receptor-and HN receptor-mediated prosurvival pathways in vitro Matsuoka et al, 2006). Both HN derivatives and ADNF-related peptides have also been reported to attenuate cholinotoxin-induced memory impairment in vivo (Gozes et al, 2000;Chiba et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Colivelin, consisting of ADNF and AGA-(C8R)HNG17, exhibits its neuroprotective activity by activating both ADNF receptor-and HN receptor-mediated prosurvival pathways in vitro Matsuoka et al, 2006). Both HN derivatives and ADNF-related peptides have also been reported to attenuate cholinotoxin-induced memory impairment in vivo (Gozes et al, 2000;Chiba et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The HN receptor is thought to be on the cell membrane (Hashimoto et al, 2001a, b;Nishimoto et al, 2004;Matsuoka et al, 2006) although it remains unidentified. Our recent studies have demonstrated that HN signals against ADrelevant neuronal death are intracellularly mediated by STAT3 in vitro Hashimoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations